PESAN MORAL PENDIDIKAN DALAM KISAH MŪSĀ PERSPEKTIF AL-QURAN - Hasan Luthfy At-Tamimy (LP2M Universitas PTIQ Jakarta, 2020)
Prophet Mūsā was the first Prophet from the Children of Israel and became the icon of that people. Even though his story is narrated in the Quran in many separate verses and chapters, that story describes a series of sub-stories under one title. So that, it attracts the reader's attention. What is more interesting is that, in the story of Prophet Mūsā, the perspective of the Quran contains educational values, morals (moral-ethics) and faith (theology). These three points emphasize the value of independence (physical), emotional maturity (emotional), and religious maturity (spiritual). So that it becomes an inspiration for the world of education in Indonesia. The Quranic perspective in the story of Prophet Mūsā is found under three main objectives of the moral message of education, namely; to direct people to fear Allah (Q.S. Ṭāhā [20]: 13-14), to guide all the mankind into the noble character (Q.S. al-Qaṣaṣ [28]: 14); and to uphold justice (Q.S. Ṭāhā [20]: 42-47).